The Bactericidal Effect Of Erbium, Chromium: Yttrium Scandium Gallium Garnet Laser On Contaminated SandBlasted, Large Grit, Acid-Etched Dental - Abdul Hameed N. Aldabagh; Mohammed K. Hassouni (University of Mosul, College of Dentistry, 2016)
Aims: The purpose of this study was to estimate the bactericidal effect of erbium,chromium:yttrium scandium gallium garnet 2,780nm (Er, Cr:YSGG) on contaminated sand-blasted, large grit, acid-etched (SLA) dental implant and determine the parameter that effectively detoxify the surface of implant ailed with periimplantitis before regenerative therapy of the area. Material and Methods: Implants (3.4*10mm) with SLA surfaces fixed with Enterococcus faecalis and irradiated with Er,Cr:YSGG lasers. After laser treatments, the number of remaining colony-forming units (CFUs) counted. The entire implant surface exposed uniformly in constant time and different energies. six powers were used ( 0.25, 0.5, 0.75, 1, 1.25, 1.5watt ) at 20 Hz, water 20%, air 40% with movable motions on each thread for 30 second and in non contact mode at 2 mm distance between MZ10 tip and target with H mode. Results: laser showed total bacteria reduction on the implants irradiated with 1.5W. Significant differences between measurements in the different groups at (P<0.05) were observed, depending on the used power. Conclusions: Er,Cr:YSGGlaser can be used at above parameter safelyon implant surface as disinfection tool in treatment of peri-implantitis